Electric and magnetic properties of Aurivillius-phase compounds: Bi5Ti3XO15 (X = Cu, Mn, Ni, V). Issue 11 (1st August 2018) - Zhao, Hongyang; Wang, Huan; Cheng, Zhenxiang; Fu, Qiuming; Tao, Hong; Ma, Zhibin; Jia, Tingting; Kimura, Hideo; Li, Huadong
Abstract: A series of Aurivillius-phase Bi5 Ti3 XO15 (X = Cu, Mn, Ni, V) (BTXO: BTCuO, BTMnO, BTNiO and BTVO) were successfully prepared using a modified micro-pulling down method and their electric and magnetic properties were carefully studied. BTVO is ferroelectric at room temperature with a diamagnetic behavior due to the absence of magnetic ions in the compound. BTCuO and BTNiO show apparent ferroelectric behavior at room temperature (RT), contrarily to BTMnO which shows negligible polarization. In terms of their magnetic properties, BTMnO is a weak ferromagnetic (canted antiferromagnetic) at temperatures below 19 K, while BTCuO and BTNiO are basically paramagnetic at low temperature and possible with a short-range magnetic ordering at RT. We do not have any evidence showing the coexistence of both ferroelectric polarization and long range magnetic ordering in any of these compounds.